2017
DOI: 10.1002/etc.3988
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of nickel to tropical freshwater and sediment biota: A critical literature review and gap analysis

Abstract: More than two-thirds of the world's nickel (Ni) lateritic deposits are in tropical regions, and just less than half are within South East Asia and Melanesia (SEAM). With increasing Ni mining and processing in SEAM, environmental risk assessment tools are required to ensure sustainable development. Currently, there are no tropical-specific water or sediment quality guideline values for Ni, and the appropriateness of applying guideline values derived for temperate systems (e.g., Europe) to tropical ecosystems is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 130 publications
0
25
1
Order By: Relevance
“…Ecotoxicity data for nickel are widely available. The data described in this paper were obtained from existing critical reviews of the literature, which are available for temperate [196] and tropical [197,198] ecosystems. These reviews followed data screening approaches consistent with those reported previously [181,196,199,200].…”
Section: Identification Screening and Aggregation Of Nickel Ecotoxicmentioning
confidence: 99%
See 1 more Smart Citation
“…Ecotoxicity data for nickel are widely available. The data described in this paper were obtained from existing critical reviews of the literature, which are available for temperate [196] and tropical [197,198] ecosystems. These reviews followed data screening approaches consistent with those reported previously [181,196,199,200].…”
Section: Identification Screening and Aggregation Of Nickel Ecotoxicmentioning
confidence: 99%
“…Application of these data to tropical ecosystems, which are increasingly important in terms of global nickel production, carries uncertainty because of differences in taxonomic groups (e.g., corals live only in tropical systems) and the distribution of chemistry parameters known to influence nickel toxicity. Binet et al [197] critically reviewed the literature for available nickel ecotoxicity data for tropical species, and only identified high-quality data for four species, including one unicellular alga, two vascular plants, and one invertebrate. The low number of available tropical data suggests that additional testing of key species (crustaceans, gastropods, and fish) may be necessary to develop a robust tropical dataset.…”
Section: Freshwatermentioning
confidence: 99%
“…The sensitivity of the species in response to toxic effects of ILs was analysed by SSD method. Species Sensitivity Distributions Burrlioz2.0 is one of the software used for SSD analysis [46]. Species sensitivities distributions were calculated using the Burrlioz2.0 package to obtain guideline values (GVs) for different levels of protection SSD plots from each group for all 4 bacteria were generated and shown in figures 4, 5 and 6.…”
Section: Chemical Toxicity Distributionsmentioning
confidence: 99%
“…The fast global discharge of potentially toxic elements (PTEs) into the hydrosphere has attracted serious focus due to their high bioavailability, bioaccumulation, and biomagnification potentials [1][2][3].…”
Section: Introductionmentioning
confidence: 99%